The Curve of the Clock - Woodard, Ben (Identities: Journal for Politics, Gender and Culture, 2020)
Author(s): Ben Woodard Title (English): The Curve of the Clock Journal Reference: Identities: Journal for Politics, Gender and Culture Publisher: Institute of Social Sciences and Humanities - Skopje Page Range: 62-63 Page Count: 2 Citation (English): Ben Woodard, “The Curve of the Clock,” Identities: Journal for Politics, Gender and Culture, Vol. 17, No. 1 (Summer 2020): 62-63.